Hip Resurfacing vs Total Hip Arthroplasty in Patients Younger than 35 Years: A Comparison of Revision Rates and Patient-Reported Outcomes - Drake G. LeBrun, MD, MPH (Elsevier, 2021)
Background: Hip resurfacing arthroplasty (HRA) and total hip arthroplasty (THA) are two treatment options for end-stage degenerative hip conditions. The objective of this single-center retrospective cohort study was to compare implant survival and patient-reported outcomes (PROs) in young patients (≤35 years) who underwent HRA or THA. Methods: All patients aged 35 years or younger who underwent HRA or THA with a single high-volume arthroplasty surgeon between 2004 and 2015 were reviewed. The sample included 33 THAs (26 patients) and 76 HRAs (65 patients). Five-year implant survival and minimum 2-year PROs were compared between patient cohorts. Results: Three patients in the THA group (9%) were revised within 5 years for instability (n = 1), squeaking (n = 1), or squeaking with a ceramic liner fracture (n = 1). No patients who underwent HRA were revised. The University of California, Los Angeles, activity score, modified Harris Hip score, and Hip Dysfunction and Osteoarthritis Outcome Scores for Joint Replacement increased by 74%, 64%, and 49%, respectively, among all patients. Compared to the HRA cohort, patients who underwent THA had lower preoperative and postoperative University of California, Los Angeles, activity, modified Harris Hip score, and Hip Dysfunction and Osteoarthritis Outcome Scores for Joint Replacement scores, yet there were no differences in the absolute improvements in any of the three measures between the two groups. Conclusions: Excellent functional outcomes were seen in young patients undergoing either HRA or THA. Although young patients undergoing THA started at lower preoperative baseline and postoperative PROs than patients undergoing HRA, both groups improved by an equal amount after surgery, suggesting that both HRA and THA afford a similar degree of potential improvement in a young population.